Tracing the growth of Sarawak pepper - Allan, Rhemaneeta; Daud, Adrian; Teruki, Neilson; Alwie, Aryaty; Hanim, Suraya; Alan, Ribka (Human Resource Management Academic Research Society, 2021)
This study was done to analyse the growth performance of Sarawak white and black pepper from the year 1990 to 2019. Compound Annual Growth Rate (CAGR) method was used to measure the growth performance. From the study, it is found that the area of cultivation and local consumption have increased for the overall period by 1.531 percent and 10.016 per percent per annum. The production and export performance for the overall period have decreased by -0.879 percent and -3.501 percent per annum. The findings suggest that an apt price stabilizing policy needs to be enacted to protect pepper producers from experiencing the negative impact of price fluctuations.